Soil Toxicity Around the Textile Industry in Bantul using Spinach Seeds (Amaranthus gangeticus) and Bean Sprouts (Phaseolus aureus) - Astari, Siti Alysha; Suherman, Suherman; Mudasir, Mudasir (Molekul, 2024)
The toxicity test of zinc metal in soil samples around the textile industry in Bantul on the growth of spinach (Amaranthus gangeticus) and bean sprouts (Phaseolus aureus) has been investigated in relation with the environmental assesment for the impact of industrial activities. This research was conducted to study physicochemical properties, adsorption-desorption, and zinc metal toxicity in the soil around the textile industry on the growth of spinach and bean sprouts. The study of physicochemical properties were water content, pH, electrical conductivity, ash content, total organic carbon, cation exchange capacity, metal content, and characterization using FTIR (Fourier transform infrared) spectrophotometry. Various zinc concentrations were studied for the adsorption capacity, whereas citric acid concentrations were used for the desorption. Atomic absorption spectrophotometry (AAS) was applied to measure metal concentrations for all samples. A toxicity tests were conducted on the growth of spinach and bean sprouts. The maximum zinc concentration was measured in point I, at 532.03 mg kg-1. Adsorption of zinc followed the Langmuir and Freundlich isotherms, and desorption process occurred at optimum concentration 0.7 mol L-1 citric acid and a pH of 3. In the zinc metal toxicity test, large concentration of zinc metal revealed inhibition effect on spinach and bean sprouts growth. Keywords: Adsorption, desorption, toxicity test, zinc.